PARENTS AND POLITICAL ETHICS FORMATION OF THE FIRST-TIME VOTERS IN CITY OF MAKASSAR - Yunus, Ariana; Yakub, Andi; Tamma, Sukri; Ekawaty, Dian (Universitas Padjadjaran, 2023)
This paper is based on research results conducted on first-time voters in the City of Makassar, South Sulawesi, in 2020. This paper aims to show the parent’s roles in the process of first-time voters forming initial political preferences, especially the ethics in political behavior within the widespread of social media as important information, including political information today. It affects the information for first-time voters’ political preferences formation, which at the same time has the potential to influence their understanding of ethics in politics. The fact is that social media is an open-source system where the information presented often provides bad and good information that cannot be detected earlier has made first-time voters potentially affected. It raises concerns about the potential negative effect of their behavior under the political ethics term. The unavailability of an early warning detection system on social media and the inexperience of first-time voters in receiving information wisely makes them vulnerable to receiving erroneous information. Therefore, the presence of parents is one of the hopes for this situation, including establishing moral and ethical understanding related to political behavior as an essential part of maintaining the sustainability of democracy in Indonesia.